Parenteral versus enteral nutrition in children with post-surgical congenital heart disease - Alakeel, Yousif S.; Ismail, Wisam W.; Alrubayan, Nasser I.; Almajed, Mohammed A. (International Journal of Health Sciences, 2021)
Objective: The association of malnutrition with congenital heart disease (CHD) is well documented. Studies comparing the effects of parenteral nutrition (PN) and enteral feeding (EF) on the post-surgical correction of CHD are not available. We compared the effects of PN with EF on the nutritional status of children post-cardiac surgery. Methods: A retrospective cohort study was conducted with 72 children aged ≤6 years who had at least one heart surgery between 2010 and 2016. Malnutrition was defined as a weight for height Z-score (WHZ) below −2. The primary endpoint was the change in the mean WHZ Z-score from the baseline. All statistical analyses were performed using SPSS 21.0 [Release 21.0.0.0, IBM, USA]. Results: The sample size realized as 72 (n = 72). The overall prevalence of malnutrition was 48%. The change in height of the PN group was significantly higher than the EF group (14.2 ± 7.6 cm vs. 7.4 ± 6.3, P = 0.010), but the weight change was not significantly different (P = 0.28). The post-surgery Z-scores were significantly lower in the PN group and the Z-score change was marginally smaller (P = 0.086), indicating lower growth levels post-surgery. The PN group had a significantly higher incidence of post-surgical malnutrition (P = 0.046). Patients who received PN had significantly less improvement (more negative change) in the Z-score levels compared to the EF group (PE = −1.42, 95% confidence interval [CI] = [−2.48, −0.35]; P = 0.011). Conclusion: Malnutrition occurs frequently with CHD. PN does not add any nutritional benefits compared with EF. EF should always be the preferred method of nutrition unless contraindicated.